Achieving cooperation with many prisoners in the NIPD. (2016) - Agudo, J. Enrique; Fyfe, Colin
This paper discusses an empirical investigation into the N-person's iterated prisoners' dilemma (NIPD), a standard problem from game theory. We use both the cross entropy method and reinforcement learning and achieve cooperation with much greater sizes of population than we have previously been able to do with genetic algorithms and artificial immune systems. Our experimental results give some insight into the circumstances where cooperation might develop.